International human resource management : managing people in a multinational context - Dowling, Peter; Schuler, Randall S.; Welch, Denice E. (Cincinnati, OH : South-Western College, 1999)
This book is about: The organizational context; International recruitment and selection; Performance management; Training and development; ...
Keywords: Management; Business enterprises; International business enterprises -- Personnel management